2005
DOI: 10.1002/ccd.20311
|View full text |Cite
|
Sign up to set email alerts
|

Stenting vs. balloon angioplasty for discrete unoperated coarctation of the aorta in adolescents and adults

Abstract: More information is needed to clarify whether stenting is superior to balloon angioplasty (BA) for unoperated coarctation of the aorta (CoA). From September 1997, 21 consecutive adolescents and adults (24 +/- 11 years) with discrete CoA underwent stenting (G1). The results were compared to those achieved by BA performed in historical group of 15 patients (18 +/- 10 years; P = 0.103; G2). After the procedure, systolic gradient reduction was higher (99% +/- 2% vs. 87% +/- 17%; P = 0.015), residual gradients lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
1
18

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 57 publications
6
79
1
18
Order By: Relevance
“…For the primary analysis, we identified 15 stenting studies or study arms with 423 participants, 12 balloon dilatation studies or study arms with 361 participants, 2 studies comparing the 2 interventions, 30,31 and 1 study comparing stenting with surgery 32 ( Figure 2A; full list of included studies is provided in the Data Supplement). Mean follow-up time ranged from 1 to 12 years in balloon dilatation studies and from 10 months to 4.7 years in stenting studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the primary analysis, we identified 15 stenting studies or study arms with 423 participants, 12 balloon dilatation studies or study arms with 361 participants, 2 studies comparing the 2 interventions, 30,31 and 1 study comparing stenting with surgery 32 ( Figure 2A; full list of included studies is provided in the Data Supplement). Mean follow-up time ranged from 1 to 12 years in balloon dilatation studies and from 10 months to 4.7 years in stenting studies.…”
Section: Resultsmentioning
confidence: 99%
“…For variables that were statistically significantly different between groups, and other variables that were considered to have a systematic effect on outcomes, we constructed forest plots to examine any potential effect on 4 key outcomes: proportion of patients achieving a gradient reduction ≤20 mm Hg; proportion achieving a gradient reduction ≤10 mm Hg; 30-day mortality; proportion of patients with severe complications before discharge. An example is Figure 3,30,31,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] which demonstrates that for both interventions, average pretreatment blood pressure gradient ( Figure 3A) and proportion of patients with native coarctation ( Figure 3B) do not systematically influence the proportion of patients with successful treatment. Further exploration of the effect of patient baseline characteristics on key outcomes is provided in Figures SI-SXII in the Data Supplement).…”
Section: Exploration Of Differences Between Patients Undergoing Ballomentioning
confidence: 99%
See 1 more Smart Citation
“…It is the basis for making the decision whether PTA, stent placement, or surgery should be performed and allows potential complications such as vessel-wall abnormalities to be assessed. [1][2][3]17 Several studies have reported evaluation of the function and anatomy of CoA using velocity-encoded cine MRI and contrast-enhanced magnetic resonance angiography. 15,31 Assessment of pressure gradients across a vascular stenosis is limited when velocity-encoded cine MRI is used because of spin dephasing, which accompanies turbulent blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the morphology of the stenosis, its hemodynamic severity, the age of the patient, and other associated cardiovascular malformations, CoA may be treated by percutaneous transluminal balloon angioplasty (PTA), endovascular stent placement, or surgery. [1][2][3] However, restenosis or aneurysm formation can occur after interventional or surgical treatment. 4 -6 Therefore, patients need careful follow-up with repeated cardiac catheterization sessions to evaluate the hemodynamic severity of the stenosis and optionally to reintervene if this is indicated and possible.…”
mentioning
confidence: 99%